Correspondence Development Seminar for Jayamulya Village Apparatus, Kroya District, Indramayu Regency - Tedy Sutrisno; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
Community service activities are carried out at the Jayamulya Village Office, Kroya District, Indramayu Regency. The village office is a government institution at the village level that is tasked with serving the administrative needs and interests of the village community. The total number of village officials is 13 people. Based on initial observations made by the implementing team to the Jayamulya Village Head and Village Secretary, they still have difficulty understanding correspondence, especially letters. This is due to educational factors, the background of village officials is predominantly high school/vocational school education. Therefore, the implementing team has the initiative to provide a solution to this problem, namely by providing an understanding through a Correspondence Development Seminar regarding correspondence to village officials. In organizing a correspondence seminar for village officials, several methods can be used to ensure that the activity runs effectively and efficiently, namely inviting speakers to explain the basic concepts, rules, and procedures for good and correct correspondence, providing examples of good and bad letters to be analyzed by seminar participants who are then asked to provide suggestions for improvement and rewrite the letter, and a question and answer session where participants can ask the resource person directly about the problems or difficulties they face in correspondence. Data collection from this activity, namely the author created pre-test and post-test questions via google form to find out to what extent the seminar has been useful and what needs to be improved for the next activity. The obstacles in implementing this program are the control experienced by village officials, namely not all village officials have adequate educational backgrounds or experience in official correspondence, making it difficult to understand the material presented, then the use of technical terms or language that is too formal can be an obstacle for participants who are not used to it, especially in areas that use local languages ​​​​everyday. The purpose of this service is that it is hoped that the correspondence seminar can provide a comprehensive and practical understanding to village officials, so that they can improve their skills in official correspondence. The result of this activity is that by carrying out this seminar activity program, seen from the filling of the pre-test and post-test carried out, the seminar participants experienced quite good improvement. Therefore, the program we carried out achieved success. Furthermore, the results of this supporting program are expected to be useful for the compiler in particular, and seminar participants in general.